Synthesis of Metallic / Metallic Oxide Nanoparticles in Surfactant Shell and Investigating their Anti- bacterial Activities - Alaa Qassen Abd El-kareem Al-Haj Qassem (My University, 2013)
With the increasing bacterial resistance for antibiotics, the demand for alternative agents is increased. Scientists go on for nanoparticles, a nanoscale material ranging from 1-100 nanometers. One of the famous nanoparticles is zinc oxide nanoparticle which is one of metal oxide nanoparticles that possess many properties such as semiconducting properties, antibacterial activity. Cobalt oxide nanoparticles, on the other hand, have less antibacterial activity research concerns. In this study, the two kinds of the nanoparticles, ZnO and CoO nanoparticles, were synthesized using chemical reduction method in different forms: the nanoparticle alone, the nanoparticle stabilized in tetra octyl ammonium bromide (TOAB) and the nanoparticle stabilized in surfactants and mixed with three diffrent types of antibiotic; Amoxicillin, Cephalexin and Streptomycin. Then, the antibacterial activity of prepared nanoparticles were studied on three bacterial strains, S. aureus, B. subtilis and E. coli. Antibacterial activity of each preparation was tested separately. Antibacterial activity of the synthesized nanoparticles showed a noticeable increase when stabilized in TOAB surfactant. Interestingly, the antibacterial activity is several times increased by the addition of the antibiotics to the NPs stabilized in TOAB; it seems that the nanoparticles stabilized in TOAB and mixed with antibiotics have synergestic effect in inhibition of bacterial growth. Interestingly, the results indicated that CoO NPs stabilized in surfactants and mixed with antibiotics have more significant increase in the antibacterial activity against the three types of bacteria in comparison to the comparable ZnO nanoparticles preparation. Therefore, this study opened the new door to find the magic cure against the multidrug resistant bacterial strains with the lowest toxic effect of the usage of high doses of the different antibiotics and nanoparticles. Key words: Zinc oxide nanoparticles, Cobalt oxide nanoparticles, Tetraoctyl ammonium bromide, S. aureus, B. subtilis, E. coli, Amoxicillin, Cephalexin, Streotomycin.

أدت زيادة المقاومة البكتيرية للمضادات الحيوية الى زيادة الطلب على ايجاد العوامل والعلاجات البديلة. من هذه العوامل البديلة استخدم العلماء المركبات والمواد النانوية والتي يتراوح أحجامها من1-100 نانومتر. أحد أكثر هذة المواد النانوية شهرة هو أكسيد الزنك النانوي والذي يعد من أشهر أكاسيد المعادن التي تمتلك العديد من الخصائص واهمها خصائص شبه الموصلة والنشاط المضاد للبكتيريا والذي حاز على اهتمام كبير كعلاج مضاد للجراثيم. من الناحية الأخرى يوجد العديد من المواد النانوية مثل أكسيد الكوبالت والذي لم يكن له نفس درجة الاهتمام كمضاد للبكتيريا كاكسيد الزنك ولكن له استخدامات واهتمامات بحثية اخرى مثل الموصلات المعدنية ولكن قليلا ما يوجد اهتمام به كمضاد للجراثيم. في هذه الدراسة، تمت صناعة المركبين النانوين المذكورين اعلاه، مركبات أكسيد الزنك وأكسيد الكوبالت النانوية باشكال مختلفة لوحدها أو تثبيتها مع المعالجات السطحية أو خلطها مع مضادات الاموكسيلين والسيفلكسين والستربتوميسسن. دراسة التاثيير المضاد للبكتيريا لهذه المواد النانوية على عزلات بكتيريا الستافيلوكوكس والايشريشيا والباسيلس لمختلف هذه التحضيرات. أشارت هذه الدراسة الى زيادة التاثير على البكتيريا بعد تغليف المواد النانوية بالمركبات ذات التاثير السطحي ولكن التاثير كان أوضح بشكل كبير عند استخدام خليط من هذه المواد النانوية المثبته بالمواد السطحية مع المضادات الحيويه، الاموكسيلين والسيفلكسين والستربتوميسسن. يبدو ان ظاهرة الدعم من المواد النانوية المثبته بالمواد السطحية والمضادات الحيويه كانت السبب في الزيادة الكبيرة لهذه المواد كمضادات حيوية. من المثير للاهتمام، أشارت نتائج هذه الدراسة إلى أن التاثير المضاد للبكتيريا لمركب أكسيد الكوبالت النانوي والمثبت بالمركبات الفعاله سطحيا والمخلوط بالمضادات الحيويه بان له تاثيرا أكبر بكثير مقارنة بالمركبات المحضره من أكسيد الزنك، ضد الثلاث أنواع البكتيريا المستخدمة في هذه الدراسة. لذلك، فتحت هذه الدراسة الباب الجديد للعثور على علاج سحري ضد سلالات البكتيريا المقاومة للأدوية المتعددة مع تأثير أقل سمية نتيجة استخدام جرعات عالية من المضادات الحيوية المختلفة والجسيمات النانوية.
تحضير المعادن وأكاسيد المعادن بأحجام النانو وتغليفها بالمذيبات السطحية ودراسة تأثيرها كمضادات بكتيرية